2006
DOI: 10.1590/s1516-89132006000300005
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological studies of Cordia salicifolia Cham in normal and diabetic rats

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 5 publications
1
13
0
1
Order By: Relevance
“…Previous studies revealed that C. ecalyculata extract shows inhibitory effects against herpes simplex virus type I (Hayashi et al, 1990), and has cardiotonic properties (Matsunaga et al, 1997), hypolipidemic effects (Siqueira et al, 2006), and cytotoxicity against certain types of tumor cells (Arisawa, 1994). The plant is characterized by high concentrations of caffeine, potassium, allantoic acid, and allantoin (Menghini et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that C. ecalyculata extract shows inhibitory effects against herpes simplex virus type I (Hayashi et al, 1990), and has cardiotonic properties (Matsunaga et al, 1997), hypolipidemic effects (Siqueira et al, 2006), and cytotoxicity against certain types of tumor cells (Arisawa, 1994). The plant is characterized by high concentrations of caffeine, potassium, allantoic acid, and allantoin (Menghini et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Since our fi rst study demonstrating antidiabetic properties of Stevia rebaudiana leaves (Curi et al, 1986), we have been investigating the hypotensive , antiobesity (Siqueira et al, 2006), hypolipidemic (Silva et al, 2004) and antidiabetic (Galletto et al, 2004) properties of the Brazilian plants.…”
Section: Resultsmentioning
confidence: 99%
“…Carnitine deficiency was obtained by the induction of diabetes. For this purpose, the rats received an intravenous injection (caudal vein) of alloxan (40 mg.kg -1 ) as previously described (Siqueira et al 2006). The control rats received an intravenous injection (caudal vein) of saline.…”
Section: Animalsmentioning
confidence: 99%
“…Therefore, a relevant aspect of the LC supplementation is a lipid-lowering effect observed in the experimental animals (Brady et al 1986;Bell et al 1987;Maccari et al 1987;Feng et al 2001;Hong et al 2002;Rajasekar and Anuradha 2007) and human (Bellinghieri et al 2003;Llias et al 2004;Guarnieri et al 2007;Cha 2008;Bernard et al 2008). On the other hand, diabetes promotes carnitine deficiency (Mamoulakis et al 2004) and increased blood triacylglycerol (Siqueira et al 2006). However, studies investigating the effect of carnitine supplementation on the blood levels of triacylglycerol in type 1 diabetes are absent, not only in the human but also in the experimental animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation